NONLINEAR TIME SERIES ANALYSIS OF THE IONOSPHERIC MEASUREMENTS - Karpenko A.L.; Manaenkova N.I. (My University, 1996)
The applications of the tools of nonlinear time-series analysis to measurements obtained by digital ionosonde “PARUS,” created at IZMIRAN, is considered. Small-scale structure of the electron density Ne at F-region of ionosphere is examined by exploring observables of reflected high-frequency radio wave. Time series corresponding to given transmitter frequency f and virtual height h and conforming to usual, not perturbed, day ionogram are examined. Using the standard correlation algorithm, we have determined that for an embedding dimension n = 15, computed correlation dimension D2(n) reaches its saturation, D2 ≃ 4. Reliability of the estimation of the correlation dimension was confirmed by applying to our sets of measurements J. Theiler's modification of standard algorithm. The test of time difference, smoothing procedure, calculation of the largest Liapounov exponent, and analysis of the surrogate data were employed in our study of data sets. Although our sets of measurements contain a significant “random noise”, nonlinear time-series analysis clear up, that the dynamics of unperturbed ionosphere, generating this time series, exhibits low-dimensional behavior.